<DATA REPORT>RECORDS OF RADIO AURORA AT SYOWA STATION, ANTARCTICA IN 1996 - YUMISASHI, Isamu; KUNITAKE, Manabu; IGARASHI, Kiyoshi (National Institute of Polar Research, 1998)
P(論文) departmental bulletin paper